Emerging innovations on exosome-based onco-therapeutics - Dai, Xiaofeng; Ye, Yongju; He, Fule (Frontiers in Immunology, 2022)
Exosomes, nano-sized extracellular vesicles for intercellular communications, are gaining rapid momentum as a novel strategy for the diagnosis and therapeutics of a spectrum of diseases including cancers. Secreted by various cell sources, exosomes pertain numerous functionalities from their parental cells and have enhanced stability that enable them with many features favorable for clinical use and commercialization. This paper focuses on the possible roles of exosomes in cancer therapeutics and reviews current exosome-based innovations toward enhanced cancer management and challenges that limit their clinical translation. Importantly, this paper casts insights on how cold atmospheric plasma, an emerging anticancer strategy, may aid in innovations on exosome-based onco-therapeutics toward improved control over cancers.